ASSESSMENT TECHNIQUES FOR MEASURING DIGITAL COMPETENCE GROWTH IN MOBILE-SUPPORTED ENGLISH CLASSES - Yuldashev Sherzod Zairjanovich; Taryanikova Marina Anatolievna (Bright Mind Publishing, 2025)
The twenty-first century has witnessed an unprecedented acceleration in digital transformation, redefining how individuals communicate, work, and learn. Educational systems across the world have entered an era dominated by rapid technological change, in which digital competence has become as essential as traditional literacy.
Keywords: Digital competence; mobile learning; MALL; English language teaching; assessment; learning analytics; digital portfolios; higher education; Kahoot; Gimkit; Quizlet; DigComp; ISTE; digital literacy.